Kreasi Cantik Warisan Budaya : Bros Jilbab dan Jepit Rambut dari Kain Songket - Vella Adelia; Nelsy Helmilia Putri; Ilham Hudi; Wingki Sarmila; Syarifatul Hayati; Amelia Nurlita; Rahma Maulida Erizal; Putri Fauzelly Mulia; Annisa Safitra; Elda Amelia (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research is a form of community service. This activity aims to develop creative skills, build entrepreneurial spirit, and increase awareness of the importance of maintaining local cultural values. Because the preservation of songket cloth as a cultural heritage and form of local wisdom of Indonesia faces challenges amidst the flow of modernization and declining interest of the younger generation. To overcome this, socialization and training activities were carried out on making hijab brooches and hair clips from songket cloth for housewives in the Bukit Barisan Housing Complex, Pekanbaru. Data collection techniques in qualitative research are by conducting observations, interviews, and documentation results. The results of this study indicate that participants are able to understand the techniques of making accessories, are enthusiastic about innovating, and show interest in developing small businesses based on local products. This activity proves that the use of local wisdom through an educational and creative approach can be a strategy for economic empowerment as well as cultural preservation.